(3GdJWhjY GdbVGFj ddbhGYO GdbGfhfjI GdhGLHI GdJWHjb aj eLGd YbhO GdJLGQI GdOhdjIs - (3ehSi(B, (3eMeO GHQGgjes ((3GdGScfOQjIs (3OGQ GdLGeYI GdLOjOI ddfTQs, 2005)
(3JgjFI bGfhf GdYbO habG debJVjGJ GdJLGQI GdOhdjI, VhGHW JgjFI bGfhf GdYbO, cjajI eWGHbI GdbhGYO GdbGfhfjI GdhGLHI GdJWHjb Ydi YbhO GdJLGQI GdOhdjI(B.s
Keywords: (3GdYbhOs; (3GdYbhO GdJLGQjIs; (3GdYbhO GdJLGQjI GdOhdjI s; (3GdbGfhf GdJLGQjs; (3GdbGfhf GdOhdj GdJLGQjs; (3YbhO GdHjY GdOhdjIs